VD_FINDINFO HC / 2020 / 600 vom 4. Oktober 2019 - VD Tribunal cantonal (2019)
CHOSE JUGÉE, CONCLUSIONS, INTERPRÉTATIONSENS GÉNÉRAL, DROIT DE PASSAGE NÉCESSAIRE | 694 CC, 58 al. 1 CPC (CH), 59 al. 1 CPC (CH), 59 al. 2 let. e CPC (CH), 83 al. 1 CPC (CH)